Apocynaceae endémicas del Perú - León, Blanca (2006)
The Apocynaceae are represented in Peru by 37 genera and 158 species (Brako & Zarucchi, 1993; Ulloa Ulloa et al., 2004), basically vines and lianas. Here we recognize 14 endemic species in 10 genera. The endemic taxa are found in several ecological regions, mainly the Very Humid Montane, Premontane and Humid Lowland Amazonian Forest regions, between 130 and 3000 m elevation. We applied IUCN categories and criteria to eight species. Only one endemic Apocynaceae is represented within Peru’s protected areas system.